2013
DOI: 10.4149/bll_2013_104
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expression of TNF-alpha and TGF-beta3 in intrinsic ureteropelvic junction obstruction

Abstract: Abstract:Objectives: Ureteropelvic junction (UPJ) obstruction is of critical importance to understand the histopathology of UPJ obstruction in terms of therapy planning and follow-up. For this purpose, our study was conducted with TNF-α and TGF-β markers to investigate possible underlying problems in intrinsic UPJ obstruction. Methods: Of the patients who had undergone surgery in our clinic, 36 UPJ segments of patients who had undergone dismembered pyeloplasty surgery due to UPJ obstruction and 14 UPJ segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, it is worth mentioning that out of these studies, we could only identify one when polymerase chain reaction (PCR) analysis was applied in human ureters and showed that the amount of TGFβ1 mRNA in stenotic tissue was higher than in controls [18]. Another study found that immunohistochemical staining of TGFβ3 in obstructed tissue was higher than in the control tissue [19]. Even though the results of our study of TGFβ in patients with PUJO could not replicate these findings, this could be due to the observations that TGFβ1 is often expressed in the early stages of diseases, especially when macrophage activity is high, as well as when inflammation is present.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth mentioning that out of these studies, we could only identify one when polymerase chain reaction (PCR) analysis was applied in human ureters and showed that the amount of TGFβ1 mRNA in stenotic tissue was higher than in controls [18]. Another study found that immunohistochemical staining of TGFβ3 in obstructed tissue was higher than in the control tissue [19]. Even though the results of our study of TGFβ in patients with PUJO could not replicate these findings, this could be due to the observations that TGFβ1 is often expressed in the early stages of diseases, especially when macrophage activity is high, as well as when inflammation is present.…”
Section: Discussionmentioning
confidence: 99%
“…A PCN catheter should remain inserted for about 4-12 weeks [1], but patients with PCN drainage are at increased risk of further renal function loss and infection [4,11]. Transforming growth factor-β and urinary tubular enzymes have also been used to predict the recoverability of renal function after the relief from obstruction, though the efficacy and feasibility of these biological agents need further evaluation [14,15]. Renal biopsy may cause infection and bleeding, and given that the histopathological changes in the kidneys are often heterogeneous, the biopsy sample may not reflect the true extent of the effects of UPJO [11].…”
Section: Discussionmentioning
confidence: 99%